Complex scaling in relativistic calculations of cross sections for electron-ion recombination processes. Issue 14 (January 2020) - Bondarev, A I; Zaytsev, V A; Shabaev, V M; Ma, X
Synopsis: We present an approach to calculate cross sections for electron-ion recombination processes. It is based on the combination of relativistic many-body perturbation theory and complex scaling method. A preliminary comparison between measured and calculated spectra for the electron-ion recombination rate coefficients for Be-like Ca will be given.